ANALISIS STRUKTUR LAPISAN BAWAH PERMUKAAN DENGAN METODE GEOLISTRIK DALAM PERENCANAAN PONDASI - Meriana Wahyu Nugroho; Fatma Ayu Nuning Farida A; Khodijah Maya (Litbang Pemas - Universitas Islam Lamongan, 2018)
The purpose of this study was to determine the structure of the subsurface at construction site Campus Rector Building B University Hasyim Ashari. Information subsurface structure used as the initial study foundation design. The research was carried out with resistivity geoelectric method using a resistivity meter. Interpretation of the track point J.01 - J.02 - J.03 known subsurface water dominated by basalt rocks, and discovered the hard ground at a depth of 12 m for planning the foundation beams, while on the track J.04 - J.02 - J.05 dominated by conglomerates and basalt rocks, and discovered the hard ground at a depth of 7 m to pile foundation design.